Enhancing Financial Planning Through Human-AI Collaborative Analytics: A Strategic Framework - Harsh Singh, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative potential of artificial intelligence (AI) in Financial Planning and Analysis (FP&A). By integrating machine learning algorithms and advanced analytics with human expertise, financial institutions can improve decision-making, streamline processes, and enhance predictive accuracy. While AI enables automation and data-driven insights, this paper underscores the need for strategic human oversight to ensure relevance and reliability. Through an exploration of industry practices, emerging trends, and implementation strategies, this article provides a roadmap for organizations adopting AI in FP&A, emphasizing the importance of robust infrastructure, change management, and human-AI collaboration for successful deployment.
Keywords: Financial Planning and Analysis (FP&A); Human-AI Collaboration; Predictive Analytics; Change Management; Machine Learning